Sex, Love and Security: Accounts of Distance and Commitment in Living Apart Together Relationships. (June 2016) - Carter, Julia; Duncan, Simon; Stoilova, Mariya; Phillips, Miranda
Drawing on a 2011 national survey and 50 semi-structured interviews, we explore the differing ways in which those in living apart together (LAT) relationships discuss and experience notions of commitment. We found that sexual exclusivity in LAT relationships is expected by the large majority, regardless of their reasons for living apart. The majority of the interviewees also expressed a high degree of commitment to their partner in terms of love, care and intimacy, alongside an appreciation of the increased freedom and autonomy that living apart has to offer. Respondents were divided into four groups according to their perceived commitment: 1. Autonomous commitment, 2. Contingent commitment, 3. Ambivalent commitment, and 4. Limited commitment. Despite differing degrees of commitment, however, the overall finding was that the importance of relating and making relational decisions was central, even in the lives of those living in such unconventional relationship styles.